2005
DOI: 10.1111/j.1600-6143.2004.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Operationally Tolerant and Minimally Immunosuppressed Kidney Recipients Display Strongly Altered Blood T-Cell Clonal Regulation

Abstract: †These authors contributed equally to this work.Most kidney transplant recipients who discontinue immunosuppression reject their graft. Nevertheless, a small number do not, suggesting that allogeneic tolerance state (referred to operational tolerance) is achievable in humans. So far, however, the rarity of such patients has limited their study. Because operational tolerance could be linked to anergy, ignorance or to an active regulatory mechanism, we analyzed the blood T-cell repertoire usage of these patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
9

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 38 publications
1
56
1
9
Order By: Relevance
“…RA is a systemic disease, with the synovial tissue as its primary target. Studies in organ-specific immune-mediated inflammatory diseases (27,42) demonstrated that specific alterations of the CDR3 LD can be observed in the peripheral blood compartment. However, we could not detect such alterations in RA peripheral blood T cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RA is a systemic disease, with the synovial tissue as its primary target. Studies in organ-specific immune-mediated inflammatory diseases (27,42) demonstrated that specific alterations of the CDR3 LD can be observed in the peripheral blood compartment. However, we could not detect such alterations in RA peripheral blood T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that naive T cells are undetectable in synovial tissue and that most synovial T cells are memory T cells (52). On the other hand, the data on CD4 versus CD8 clonal alterations in RA are in conflict: the most prominent clonal expansions are often found in the CD8ϩ populations in RA (53) as well other pathologic conditions (27,42), whereas other studies have demonstrated clear clonal alterations in the CD4ϩ populations (47,50,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the frequency of this observation in the kidney transplant population is unknown and, currently, we cannot identify patients primed to develop this immune adaptation or monitor for the stability of this status of ''operational tolerance.' ' The operationally tolerant kidney transplant patients in this study have been previously described (8) and show an altered T cellreceptor repertoire (9) and distinct lymphocyte phenotypes (10). However, none of these observations have been validated as being functionally involved in operational tolerance in humans.…”
mentioning
confidence: 80%
“…Approximately 100 cases of operational tolerance in renal transplant have been reported (Orlando et al 2010) with a denominator of many tens of thousands of total kidney transplants. There are a steadily increasing number of reports of different immune monitoring phenotypes or "signatures" that characterize tolerant recipients (Brouard et al 2005Newell and Larsen 2006;Einecke et al 2010;Newell et al 2010;Sagoo et al 2010). It may be possible to use these combined signatures to identify candidates for immunosuppression weaning.…”
Section: Planned Immunosuppression Weaningmentioning
confidence: 99%